Comorbidities in Patients with COVID-19 and Their Impact on the Severity of the Disease - Bashir, Shahid; Moneeba, Sadaf; Alghamdi, Alaa; Alghamdi, Fouad; Niaz, Asim; Anan, Hadeel; Kaleem, Imdad (Journal of Health and Allied Sciences NU, 2020)
Infection with COVID-19 is associated with significant morbidity, especially in patients with chronic medical conditions. At least one-fifth of cases require supportive care in intensive care units, which have limited availability in most developing countries. A literature search was conducted on PubMed, Medline, Scopus, Embase, and Google Scholar to find articles published by May 7, 2020 on the role of comorbidities in patients with COVID-19 and the impact of comorbidities on the disease. This review highlighted that patients with comorbidities are more likely to experience severe disease than those with no other conditions; that is, comorbidities correlated with greater disease severity in patients with COVID-19. Proper screening of COVID-19 patients should include careful inquiries into their medical history; this will help healthcare providers identify patients who are more likely to develop serious disease or experience adverse outcomes. Better protection should also be given to patients with COVID-19 and comorbidities upon confirmation of the diagnosis. This literature review showed that the comorbidities most often associated with more severe cases of COVID-19 are hypertension, cardiovascular disease, and diabetes. Individuals with these comorbidities should adopt restrictive measures to prevent exposure to COVID-19, given their higher risk of severe disease.
Keywords: COVID-19; morbidity; comorbidities; pandemic